PERANAN AUDITOR SYARIAH PADA SISTEM JAMINAN HALAL DI BANK SYARIAH - Malahayatie Malahayatie (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
This article aims to provide a description of the role of auditors Sharia halal assurance system in Islamic banking in Indonesia.. Syariah banking is as finance institution should be checked and experimented smartly, product, and it’s operational by an independent institution that is an “syariah auditor” and should be paid an attention by syariah auditor that is the finance report of Syariah bank, SOP (System Operating Procedures), Syariah Human resoource (HR), Syariah monitoring Council, and structure of syariah product. The moitorig of syari’ah bank as well as monitored by internal or external syari’ah auditor, while the guarantee in Islamic law divided into two their consisted of : personal guarantee and property guarantee and known as “kafalah or rahn”. The institution that control or monitor that’s internal or external syariah auditor should do the syariah internal review that was done by syariah compliance officer, that control or monitor the syari’ah compliance and decision ”fatwa”, instruction, guideline, that issued by Syariah monitoring Council in that finance institution. Syariah review, internal of syariah review and syariah auditing is an important process to ensure the halal guarantee system to the operational activity of syariah finance institution and it’s syariah products. The report and recomendation from the Syariah monitoring Council willbe given to National Syariah monitoring Council as the consideration. Keyword: Auditor, Halal Guarantee, National Syariah Council